Empowerment of Siwalan Processed Small Enterprises Group Through Strengthening GMP (Good Manufacturing Practice) in Tuban Regency - Widya Dwi Rukmi Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2021)
Siwalan is palm type plants, which one of the prime agricultural commodities in Tuban Regency. Siwalan production has increased from year to year. Abundant production provides great potential for siwalan farmers and groups of siwalan processed enterprises into other processed products. So far, technological innovation has not touched on the processing of legen or siwalan fruit, so that the development of its marketing is very limited and it has not been able to broader the welfare of society. The purpose of this activity is to examine the relationship between aspects of attitude towards food security with aspects of business performance and the importance on strengthening GMP (Good Manufacturing Practice).